Evaluation of the reality of university activities in the Colleges of Basic Education (Journal of the College of Basic Education, 2022)
To develop the educational process, it is necessary to pay attention to the aspects affecting it, which are summarized in the curriculum, the teacher, the educational environment, student activities, classroom and non-classroom, and evaluation methods. These are aspects that cannot be separated from each other if we want a real comprehensive and scientific development rather than a partial one. Thus, the integration of the development of these aspects will achieve the desired development of the educational process.The researchers noticed, from their experience in university teaching, the lack of interest in providing a special atmosphere for that.